Sporotrichosis in Iran: A mini review of reported cases in patients suspected to cutaneous leishmaniasis - shahram mahmoudi; farideh zaini (Mazandaran University of Medical Sciences, 2015)
Sporotrichosis is a chronic subcutaneous fungal infection with global distribution. It is a rare fungal infection with nine reported cases in Iran, including eight humans and one animal, within the past 30 years. Among the human cases, seven were of the fixed cutaneous type of sporotrichosis and one had sporotrichoid lymphocutaneous. The reported patients were within the age range of 23-60 years, and six of them were female. The most frequent sites of infection were forearms and hands, as well as the face and legs. In addition, the majority of the cases had previously been suspected of leishmaniasis and received treatment. Sporotrichosis is not a well-known condition in Iran and is often misdiagnosed and erroneously treated for other cutaneous parasitic or bacterial infections with similar clinical manifestations. Therefore, sporotrichosis should be taken into account in the differential diagnosis of nodular-ulcerative skin lesions.